Sea ice, temperature, and prey effects on annual variations in mean lengths of a key Arctic fish, Boreogadus saida, in the Barents Sea. (3rd May 2020) - Dupont, Nicolas; Durant, Joël M; Langangen, Øystein; Gjøsæter, Harald; Stige, Leif Christian
Abstract: Oceanographic conditions in the Arctic are changing, with sea ice cover decreasing and sea temperatures increasing. Our understanding of the effects on marine populations in the area is, however, limited. Here, we focus on the Barents Sea stock of polar cod ( Boreogadus saida ). Polar cod is a key fish species for the transfer of energy from zooplankton to higher trophic levels in the Arctic food web. We analyse the relationships between 30-year data series on the length-at-age of polar cod cohorts (ages 0–4) and sea surface temperature, sea ice concentration, prey biomasses, predator indices, and length-at-age the previous year using multiple linear regression. Results for several ages showed that high length-at-age is significantly associated with low sea ice concentration and high length-at-age the previous year. Only length-at-age for age 1 shows a positive significant relationship with prey biomass. Our results suggest that retreating sea ice has positive effects on the growth of polar cod in the Barents Sea despite previous observations of a stagnating stock biomass and decreasing stock abundance. Our results contribute to identifying mechanisms by which climate variability affects the polar cod population, with implications for our understanding of how future climate change may affect Arctic ecosystems.